The connected species how the evolution of the human brain can save the world - Williams, Mark A. (Rowman & Littlefield, 2023)
"This book argues that by understanding human connection, we can work together toward a less divided, more sustainable, future"--
Keywords: Social participation; Belonging (Social psychology); Brain / Evolution